Growth and decomposition of major oilseeds in Madhya Pradesh (2000-01 to 2017-18): Growth and decomposition of major oilseeds in Madhya Pradesh (2000-01 to 2017-18) - PALADUGU PRAVEEN KUMAR; S V RAMANA RAO; VIJAY KUMAR CHOUDHARY; AJAY KUMAR KOSHTA (Journal of Oilseeds Research, 2020)
Madhya Pradesh occupies 27 and 24 per cent of India’s oilseeds area and production (TE 2017-18). The CAGR for area was positive for soybean, rapeseed-mustard, sesame and groundnut while area decelerated in linseed and niger. The positive CAGR for production and yield across all oilseed crops indicates sustained production due to area expansion and technology implementation. Decomposition analysis revealed that area effect had more pronounced contribution for change in production across all crops while technology (yield effect) played a crucial role for change in production of sesame, rapeseed-mustard and soybean. Technology assemblage and its large scale expansion can enable increase in the productivity of oilseed crops in Madhya Pradesh.